2020
DOI: 10.1016/j.ebiom.2020.103101
|View full text |Cite
|
Sign up to set email alerts
|

Analytical and clinical performances of five immunoassays for the detection of SARS-CoV-2 antibodies in comparison with neutralization activity

Abstract: Background Reliable high-throughput serological assays for SARS-CoV-2 antibodies are urgently needed for the effective containment of the COVID-19 pandemic, as it is of crucial importance to understand the strength and duration of immunity after infection, and to make informed decisions concerning the activation or discontinuation of physical distancing restrictions. Methods In 184 serum samples from 130 COVID-19 patients and 54 SARS-CoV-2 negative subjects, the analyti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
100
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 139 publications
(109 citation statements)
references
References 23 publications
5
100
4
Order By: Relevance
“…Whether the antibodies measured with commercial assays have a neutralizing capacity is paramount for indicating the potential level of protective immunity against SARS-CoV-2 infection. Recently, Padoan et al found that the Ortho S1 IgG (R 2 adj = 0.544) and DiaSorin S1 + S2 IgG (R 2 adj = 0.402) assays were more correlated to neutralization activity compared with the Ortho S1 total antibody (R 2 adj = 0.117) and Roche NCP total antibody (R 2 adj = 0.046) assays [ 6 ]. The fact that anti-NCP assays showed a low correlation with the neutralizing capacity was expected as neutralizing antibodies are directed against the spike protein that is responsible for enabling the entry of the virus into the cells that express ACE-2 [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whether the antibodies measured with commercial assays have a neutralizing capacity is paramount for indicating the potential level of protective immunity against SARS-CoV-2 infection. Recently, Padoan et al found that the Ortho S1 IgG (R 2 adj = 0.544) and DiaSorin S1 + S2 IgG (R 2 adj = 0.402) assays were more correlated to neutralization activity compared with the Ortho S1 total antibody (R 2 adj = 0.117) and Roche NCP total antibody (R 2 adj = 0.046) assays [ 6 ]. The fact that anti-NCP assays showed a low correlation with the neutralizing capacity was expected as neutralizing antibodies are directed against the spike protein that is responsible for enabling the entry of the virus into the cells that express ACE-2 [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Compared with commercial immunoassays, only neutralization activity assays reliably measure the actual protective immunity of antibodies [ 6 ]. However, neutralization activity assays are only reserved for specialized laboratories and require a high workload, skillful operators, expensive installations, crucial biosafety measures and have, to date, a low throughput.…”
Section: Introductionmentioning
confidence: 99%
“…While molecular tests and rapid antigen tests are targeted for early diagnosis, serology tests play a different and perhaps even larger role by supporting epidemiological studies, furthering the understanding of longitudinal immunity, and in assessing the efficacy of vaccine development [5]. The efficient use of serology tests in understanding immunity, both in response to disease or vaccination, requires evaluation of any given assay's diagnostic performance and discriminative ability [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…A high-throughput PRNT method was used for the fast and accurate quantification of neutralizing antibodies in plasma samples collected from patients exposed to SARS-CoV-2, as described elsewhere (12). Briefly, after heat-inactivation, samples were diluted in Dulbecco modified Eagle medium (DMEM) and then mixed with a virus solution containing 20-25 focus-forming units (FFUs) of SARS-CoV-2.…”
Section: Plaque Reduction Neutralization Test (Prnt)mentioning
confidence: 99%